Tren Kebijakan Penanganan Stunting di Negara-Negara Berkembang di Asia Tenggara: Peran WHO untuk Mencapai Target Global - Octavia Devi, Elvyra; Suluh Kusuma Dewi, Dian; Wahjuni DJ, Ekapti (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2023)
Stunting is a chronic nutritional problem caused by a lack of nutritional intake resulting in impaired growth in children. This study aims to map research topics and issues regarding stunting management trends in developing Southeast Asian countries. This research contributes to the development of public policy studies and provides a comparison of policies and measures taken by governments with high stunting rates. The research method applied in this study is the Systematic Literature Review (SLR) method using the Nvivo 20 and Vosviewer application as a data analysis tool. This article reviews 683 articles sourced from the dimensions database, then selected according to the criteria. The results of the research reveal that there are many trends in stunting management carried out by developing countries in Southeast Asia in accordance with the needs and capabilities of the country. Policies in Indonesia focus on improving proper sanitation, Malaysia has a nutrition intervention program carried out in every school, the Myanmar government provides special care in refugee areas to increase food diversity and adequate nutrition for children. Thailand already covers 20% of meeting food needs, especially in animal protein, especially for the poor, Vietnam has a nutrition intervention program in the form of agriculture and food security. This research is important because it provides a comparison of policies and steps taken by developing countries in Southeast Asia, especially those with high stunting rates. There are differences in the handling of stunting in each country due to the needs and capabilities of each country, but in handling it remains in accordance with the provisions of WHO.